No apparent transmission of transgenic α–synuclein into nigrostriatal dopaminergic neurons in multiple mouse models - Sastry, Namratha (Transl Neurodegener, 2015)
BACKGROUND: α–synuclein (α–syn) is the main component of intracytoplasmic inclusions deposited in the brains of patients with Parkinson’s disease (PD) and certain other neurodegenerative disorders. Recent studies have explored the ability of α–syn to propagate between or across neighboring neurons and supposedly “infect” them with a prion–like mechanism. However, much of this research has used stereotaxic injections of heterologous α–syn fibrils to induce the spreading of inclusions in the rodent brains. Whether α–syn is able to transmit from the host cells to their neighboring cells in vivo is unclear. METHODS: Using immunestaining, we examined the potential propagation of α–syn into nigrostriatal dopaminergic (DA) neurons in three lines of transgenic mice that overexpress human wild–type α–syn (hα–syn) in different neuron populations. RESULTS: After testing for three different routes by which hα–syn propagation might occur, we were unable to find any evidence that hα–syn behaved like a prion and could be transmitted overtime into the DA neurons initially lack of hα–syn expression. CONCLUSIONS: In transgenic mice hα–syn does not have the ability to propagate at pathologically significant levels between or across neurons. It must be noted that these observations do not disprove the studies that show its prion–like qualities, but rather that propagation is not detectable in transgenic models that do not use any injections of heterologous proteins or viral vectors to induce a spreading state.